The Assessment and preference of student-centered learning under subject of chemistry among Permata Pintar students - Sabrina Mohd Yusof; Nor Farhah Razak; Ikhwan Zakaria (Penerbit Universiti Kebangsaan Malaysia, 2024)
Teaching and learning chemistry at all levels of education have faced numerous challenges. These challenges include students' struggles with problem-solving skills, limited spatial visualization abilities, difficulties in grasping chemistry vocabulary, and inadequate communication between students and teachers. As a result, researchers across various educational contexts have consistently advocated for the creation of a learning methods that effectively addresses these difficulties. This research delves into an examination of the pedagogical approaches, both as currently perceived and preferred, among PERMATA@Pintar College students in the realm of chemistry education. The investigation concentrates on two primary pedagogical paradigms: student-centered teaching and teacher-centered teaching. The study encompasses a cohort of 150 students ranging in age from 13 to 18 years. To gauge the students' perceptions of their teachers' instructional methods and their own preferences, a revised version of the Approaches to Teaching Inventory (ATI) originally developed by Prosser and Trigwell was employed. The findings of this study reveal that the prevailing pedagogical approach in chemistry classes appears to strike a balance between teacher-centered and student-centered learning. However, in terms of the students' own inclinations, they exhibit a slight preference for the teacher-centered method, emphasizing information transfer, over the student-centered approach, which emphasizes conceptual change. Interestingly, when considering the desired shift in teaching methods as envisioned by the students, their preference leans significantly towards an increased frequency of student-centered methods, highlighting a distinct preference for these methods over teacher-centered ones.